Anchoring Groups Determine Conductance, Thermopower and Thermoelectric Figure of Merit of an Organic Molecular Junction - Ramezani Akbarabadi, Saeideh; Madadi Asl, Mojtaba (Frontiers in Physics, 2021)
Transport properties of molecular junctions are prone to chemical or conformational modifications. Perturbation of the molecule-electrode coupling with anchoring groups or functionalization of the molecule with side groups is a well-characterized method to modulate the thermoelectric properties of molecular junctions. In this study, we used wide-band approximation combined with the non-equilibrium Green’s function (NEGF) formalism to inspect conductance, thermopower and figure of merit of an anthracene molecule coupled to gold (Au) electrodes. To provide a comparative study, three different anchoring groups were used, i.e., thiol, isocyanide and cyanide. The molecule was then perturbed with the amine side group in two positions to explore the interplay between anchoring groups and the side group. We showed that the introduction of side group alters transmission probability near the Fermi energy where transmission peaks are shifted relative to the Fermi level compared to the unperturbed molecule (i.e., without side group), ultimately leading to modified electrical and thermoelectric properties. The greatest value of electrical conductance was achieved when the side-group-perturbed molecule was anchored with isocyanide, whereas the thiol-terminated molecule perturbed with the side group yielded the greatest value of thermal conductance. We found that the Wiedemann-Franz law is violated in the Au-anthracene-Au device. Furthermore, the highest thermopower and figure of merit were attained in the cyanide-terminated perturbed molecule. Our results indicate that charge donating/accepting character of the anchoring group and its interplay with the side group position can modify temperature dependency of conductance, thermopower and figure of merit which is in agreement with experimental findings in organic molecular junctions. Such modifications may potentially contribute to the understanding of emerging conductance-based memory devices designed to mimic the behavior of brain-like synapses.